A procedure for a choice of the operating feature dictionary for recognition of radiation sources with means of radar monitoring - Kalyuzhniy, N. M.; Galkin, S. A.; Nikolaev, I. M.; Kolesnik, V. I. (Видавництво Львівської політехніки, 2012)
Approaches to a choice of the most informative combinations of signal features are considered. The procedure for a choice of the operating feature dictionary is proposed. Probabilities of true recognition and are estimated.
Keywords: recognition; radiating sources; operating feature dictionary; probability density function